2023
DOI: 10.3389/fmicb.2023.1109972
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity and mechanism of imidazole chloride ionic liquids on Staphylococcus aureus

Abstract: Ionic liquids (ILs) have garnered increasing attention in the biomedical field due to their unique properties. Although significant research has been conducted in recent years, there is still a lack of understanding of the potential applications of ILs in the biomedical field and the underlying principles. To identify the antibacterial activity and mechanism of ILs on bacteria, we evaluated the antimicrobial potency of imidazole chloride ILs (CnMIMCl) on Staphylococcus aureus (S. aureus). The toxicity of ILs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…79 Due to the negative electrostatic charge present on bacterial cell surfaces, 80,81 the cations of ILs can easily affect the bacterial surface. 82,83 Meanwhile, the combination of different cations and anions produces a wide range of ILs with tunable structures, enabling the customization of their properties against bacteria, such as Gram-positive Staphylococcus aureus (S. aureus), Gram-negative Pseudomonas aeruginosa (P. aeruginosa), and Escherichia coli (E. coli). The tunability of ILs makes it possible for them to meet different antibacterial demands.…”
Section: Ils As Drug Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…79 Due to the negative electrostatic charge present on bacterial cell surfaces, 80,81 the cations of ILs can easily affect the bacterial surface. 82,83 Meanwhile, the combination of different cations and anions produces a wide range of ILs with tunable structures, enabling the customization of their properties against bacteria, such as Gram-positive Staphylococcus aureus (S. aureus), Gram-negative Pseudomonas aeruginosa (P. aeruginosa), and Escherichia coli (E. coli). The tunability of ILs makes it possible for them to meet different antibacterial demands.…”
Section: Ils As Drug Candidatesmentioning
confidence: 99%
“…4A). 82 Chao et al demonstrated that ILs with longer alkyl chains exhibited enhanced antibacterial effects against S. aureus and E. coli . These effects were attributed to the interplay of hydrophobic and electrostatic interactions between the ILs and bacterial membranes.…”
Section: Therapeutic Components and Mechanismmentioning
confidence: 99%
“…As a promising solvent, the properties of ionic liquids (ILs) can be tuned according to the requirements by changing the anion, cation, and functional groups, which makes them attractive for a variety of applications, such as catalysis, 1,2 electrochemistry, 3 extraction, 4,5 and solvents. 6,7 In recent years, ILs have gained significant attention in the field of biopharmaceuticals, 8 such as stabilizers to improve the stability of biomolecules, 9 drug carriers to increase the drug solubility, 10 therapeutic agents for disease treatment, 11 and components in biosensors and diagnostic platforms. 12,13 ILs have the capacity to interact with the solute and co-solvent molecules, which can disrupt existing association and promote the assimilation of the solute.…”
Section: Introductionmentioning
confidence: 99%
“…25 The scanning electron microscopy experiment shows that a high concen-tration of ILs can destroy the structure of the cell membrane, displaying the potential toxicity of ILs. 26 To characterize the effects of ILs on cell membranes and MCPs, molecular dynamics (MD) simulations are always used, especially considering the nanoscale effect of the interface between ILs and cell membranes. It is shown that electrostatic interaction from ILs could influence protein stability, 27 and the hydrophilic ILs could destroy the structure of α-lactalbumin by forming hydrogen bonds between IL and protein surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, infrared spectroscopy experiments suggest that the ILs of [C 10 mim]Cl can induce secondary structural changes in MCP and actin filaments in HeLa cells . The scanning electron microscopy experiment shows that a high concentration of ILs can destroy the structure of the cell membrane, displaying the potential toxicity of ILs . To characterize the effects of ILs on cell membranes and MCPs, molecular dynamics (MD) simulations are always used, especially considering the nanoscale effect of the interface between ILs and cell membranes.…”
Section: Introductionmentioning
confidence: 99%